Penatalaksanaan Fisioterapi Pada Kondisi Hernia Nucleus Pulposus L4-L5 Di RST Prof. Dr. Soedjono Magelang - Putra Surya, Areza; , Sugiono S.Fis, MH.Kes (2015)
Background: Herniated Nucleus Pulposus (HNP) is the state when the nucleus pulposus protruding out then pressed toward the spinal canal through annulus fibrosus in the intervertebral disc. Herniated nucleus pulposus is characterized by low back pain, muscle spasms, muscle weakness, reduced mobility and activity disorder. Aims of Research: To study about functions of Transcutaneus Electrical Nerve Stimulation and Core Stability Exercise on reduce pain, increase trunk range of motion, increase capacity of functional activity in the case of herniated nucleus pulposus. Results: After therapy for about six times the obtained results of reduction in pain at rest T0: 2 to T6: 1, tenderness T0: 4 to T6: 3, painful movement of trunk flexion T0: 5 to T6: 4, painful movement of hip flexion T0: 3 to T6: 2. Increasing in trunk flexion range of motion T0: 7 cm to T6: 9 cm, extension T0: 4 cm to T6: 4 cm, lateral flexion dextra T0: 11 cm to T6: 11cm, lateral flexion sinistra T0: 10 cm to T6: 11 cm. There is an increasing ability of functional activity T0: 18 (36%) to T6: 14 (28%). Conclusion: Transcutaneus Electrical Nerve Stimulation and Core Stability Exercise is modalities of physical therapy can be used to solve problems such as lower back pain, decreased trunk range of motion resulting in decrease ability of functional activity.